4The Inffluence of Financial Technology of MSME Financing - Muhammad, Raudatul Hasanah (UMBanjarmasin, 2023)
FinTech is type of technology based financial service that enables financial transactions without an account. With the ongoing advancement in technology, there will no doubt be a lot of changes. As a result, technology will be increasingly used to assist community activities, one of which is the economy. Fintech itself offers a number of services, including financing, investment, and payments. One of the services that can be used is P2P landing, where this site will connect those who have money and those who need money. This can help MSME finance in developing their companies by registering fintech with BANK Indonesia. The existence of fintech is expected to have a positive impact on MSME funding.